THE EFFECT OF MULTIMEDIA AND DISCIPLINARY TO BIOLOGY LEARNING ATTAINMENT OF X CLASS IN MADRASAH ALIYAH NASYRUL 'ULUM BANI SHOLEH CILEGON - Fera Purnama Sari (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2017)
The purpose of this research was to determine: (1) differences in the the achievement of Biology learning between learning with multimedia power point and learning with print media, (2) differences in the achievement of Biology learning between students who have high discipline and low discipline, (3) the effect of interaction between learning with multimedia power point and discipline on the achievement of Biology learning, (4) differences in the achievement of Biology learning between learning using multimedia power point with high discipline and learning using print media with high discipline, and (5) differences in the achievement of Biology learning between learning using multimedia powerpoint with low discipline and learning using print media with low discipline. The research of population was class X MIA, while samples are used throughout the class X MIA. This research was conducted in MA Nasyrul 'Ulum Sholeh Bani Cilegon. This research was conducted in November-December 2015. The method of the research using a quasi experimental with data analysis through Anova two ways. The results of the research showed that: (1) the achievement of Biology learning that use multimedia powerpoint better than the result of Biology learning use print media, (2) the achievement of Biology learning students who have high discipline better than students who have low discipline, (3) there is no the effect of the interaction between multimedia powerpoint and discipline on the achievement of Biology learning, (4) the achievement of Biology learning using multimedia powerpoint and high discipline higher than the result of Biology learning using print media and high discipline, (5) the achievement of Biology learning using multimedia powerpoint and low discipline no higher than the achievement of Biology learning using print media and low discipline.